Tauhid Sufistik Ibn Taymīyah ‎(Sebuah Upaya Menemukan Aspek Sufistik Ibn Taymīyah)‎ - Octaviani Erman Nanda (Departement of Comparative Study of Religions, 2021)
This article re-analyzes Ibnu Taimiyah’s position and his thought on Sufism and anti-‎Sufism. The article is also expected to find the precise typology to describe the ‎qualification of Ibnu Taimiyah’s Sufism other than the Sunni and Falsafi ‎typologies. As a formalist and literalist thinker, Ibnu Taimiyah has been famously ‎known as an anti-Sufi Muslim scholar. There have been a number of modern ‎Salafis who refute any relationship between Ibnu Taimiyah and Sufism. Ibnu Taimiyah ‎has criticized such philosophical doctrines of Sufism as waḥdat al-wujûd, ḥulûl, ‎and ittiḥâd, which are considered to have deviated from the foundations of ‎Islam. along with criticism, Ibnu Taimiyah offers a solution by recovering the earliest ‎and authentic tradition of Sufism when it is viewed as to have obscured the ‎authenticity of knowledge based on the al-Qur’an and Sunnah. The product of his ‎Sufism can be, therefore, categorized in Salafi-Sufism typology in addition to ‎other such Ibnu Taimiyah popular typologies as Sunni and Falsafi. The pattern of ‎the Tasawuf Falsafi -which is deemed as being appropriate to describe the ‎existence of Ibnu Taimiyah’s Sufism, does not, basically, accept takwîl upon ‎the religious texts. The aim of his Sufism is to strengthen one’s faith and help ‎him/her to purify their soul and morality.